The German Gītā: hermeneutics and discipline in the German reception of Indian thought, 1778 - 1831 - Herling, Bradley L. (Studies in philosophy, 2006)
Theoretical and methodological considerations -- The early flowers of India : Johann Gottfried Herder -- The Bhagavadgita and the blossoming of India in Herder's thought -- The pantheism dilemma and Friedrich Schlegel's Gītā -- August Wilhelm Schlegel's Indian Sphinx : the persistent riddle of Gītā translation -- German absorption in the Gītā : Wilhelm von Humboldt and Hegel